Релікти апелятива *volja в сучасному українсько-польському ойконімному просторі. - Редьква, Я. П. (Wydawnictwo JAK, 2021)
The productiveness and localization of modern place names with the component *volja that underwent further onymization in the 15th to 16th centuries was authenticated in the article. It signifies a new type of newly coined localities in Polish and Ukrainian oikonymy designating settlements that were free from taxes, in particular, Polish (Wola, Wolica, Wólka), Ukrainian (Воля (Volia), Волиця (Volytsia), Волька (Vol’ka)) and their derivatives. Polish and Ukrainian oikonyms with the components Wola ~ Воля (Volia) over the period of history of their use formed homogeneous structural types that are used today: single-word oikonyms, multiword oikonyms with pre- and postpositional adjectival components, and pre- and postpositional component -воля (-volia)/-волиця (-volytsia), multiword onyms: 1) Adj. + Subst. Wola, Wolica, Wólka ~ Воля (Volia), Волиця (Volytsia), Волька (Vol’ka); 2. Subst. Wola, Wolica, Wólka ~ Воля (Volia), Волиця (Volytsia), Волька (Vol’ka) + Adj. From the point of view of signification, these oikonyms denote a type of a free settlement indicating their owner or founder, geographical location, location in relation to neighbouring settlements, i.e. the differentiating and localising function of these types of onyms is emphasized. The number and geographical distributions of the oikonyms in Poland and Ukraine are presented. It was established that their highest number is in Lublin, Małopolskie, Podkarpackie and Mazowieckie Voivodeships (Poland) and in the west of Ukraine (Lviv, Volyn, Ternopil Oblasts). The naming tendencies of the further onymization of the appellative *volja in Ukrainian and Polish oikonymy were emphasized.
Keywords: appellatives (Ukrainian воля (volia), волиця (volytsia), волька (volka); Polish wola, wolica, wólka); onymization of appellatives, oikonymy, structural types of oikonyms